2018
DOI: 10.1093/icesjms/fsy140
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation strategies of coastal fishing communities as species shift poleward

Abstract: In this period of environmental change, understanding how resource users respond to such changes is critical for effective resource management and adaptation planning. Extensive work has focused on natural resource responses to environmental changes, but less has examined the response of resource users to such changes. We used an interdisciplinary approach to analyse changes in resource use among commercial trawl fishing communities in the northwest Atlantic, a region that has shown poleward shifts in harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 57 publications
3
75
0
2
Order By: Relevance
“…Many authors have called for a portfolio approach to managing fisheries that reduces barriers to diversification for fishers (e.g., Hilborn et al, 2001;Sanchirico, Smith, & Lipton, 2008;Cunningham et al, 2016). Allowing fishers increased flexibility to shift among strategies may be particularly important as species distributions shift due to global climate change (Young et al, 2018). Hilborn et al (2001) suggested that the rigidity of the management system is a major impediment to adopting a more flexible approach to fisheries governance that affords fishers more autonomy and choice in managing their risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have called for a portfolio approach to managing fisheries that reduces barriers to diversification for fishers (e.g., Hilborn et al, 2001;Sanchirico, Smith, & Lipton, 2008;Cunningham et al, 2016). Allowing fishers increased flexibility to shift among strategies may be particularly important as species distributions shift due to global climate change (Young et al, 2018). Hilborn et al (2001) suggested that the rigidity of the management system is a major impediment to adopting a more flexible approach to fisheries governance that affords fishers more autonomy and choice in managing their risk.…”
Section: Discussionmentioning
confidence: 99%
“…We used four criteria to evaluate the rigour of our case-study approach: construct validity (use of appropriate measures), internal validity (strength of casual inferences), external validity (generalizability of the findings) and reliability (replicability; Yin, 2018). Following Yin (2018), we addressed each criterion with a set of analytic tactics.…”
Section: A S E-s Tudy Approachmentioning
confidence: 99%
“…Changes to the intensity of harvest may have either dampening or amplifying feedbacks on the exploitation of target species, depending on fishers' socioeconomic characteristics and livelihood options, which influence their responses to change . Fishers may also change or rotate harvest locations (Sievanen 2014, Young et al 2019), diversify their fisheries portfolios, or shift to high-value fisheries (Perry et al 2011. Fisheries portfolio diversification reduces the risk to fishers of interannual variation in stock abundance and market value (Kasperski andHolland 2013, Finkbeiner 2015) and is a signal of fishers' adaptive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, these frameworks have not included formative evaluation of identified options or sets of alternatives. Within the body of adaptation science, a limited number of empirical studies involving forecast assessments of adaptation response options aiming to addressing climate vulnerability in fisheries have been undertaken [examples include: Koehn et al (2011), Fleming et al (2014, Pratchett et al (2017), Blair and Momtaz (2018), Miller et al (2018), and Young et al (2019)]. The range of analytical methods applied to assess adaptation options for fisheries includes:…”
Section: Introductionmentioning
confidence: 99%